Antimicrobial Effects of Propolis Incorporated Dental Composite Resin - Asad Khan, Sajid Hussain, Mamoona Shah, Noureen Naim, Zunaira Shaukat, Hafiz Muhammad Abu Bakar Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Aim/Objective: The aim of this in-vitro study is to assess the antibacterial activity of a propolis-modified experimental dental composite resin in terms of reducing and preventing recurrent caries, usually caused by Streptococcus mutans. Materials and methods: Control group specimens were made using the 70/30 (filler/resin) method without the use of EPE. Group 1 specimens were made by mixing 12% EPE with 30% resin in experimental dental composite resin. The experimental dental composite was created by adding 16%EPE and 20% EPE to Group 2 and Group 3, respectively. Antibacterial testing was carried out in the inhibition zone using the minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC). Surface roughness was assessed using scanning electron microscopy. Results: The results were evaluated using one-way ANOVA and Tukey's high significant difference test (HSD). The EPE displayed antibacterial action against S.mutans, according to the findings. The inhibitory zone of 20% EPE integrated dental composite resin was 2.2mm to 2.5mm. Inhibition zones ranging from 1.2mm to 1.8mm were found in 12% and 16% of the samples, respectively. The results of the minimum inhibitory concentration showed that 20% had stronger antibacterial activity than 12 and 16 %. Scanning electron microscopy research revealed that 20% of EPE samples had decreased surface roughness. Conclusion: The experimental dental composite showed antibacterial activity against S.mutans. Antibacterial activity is increased by increasing the proportion of EPE in the experimental composite. Due to its dark color appearance it is recommended for usage as a lining material under restorative materials.